Reduced order Galerkin models of flow around NACA‐0012 airfoil - Stankiewicz, Witold; Morzyński, Marek; Noack, Bernd R.; Tadmor, Gilead (Mathematical Modelling and Analysis, 2008)
The construction of low‐dimensional models of the flow, containing only reduced number of degrees of freedom, is the essential prerequisite of closed‐loop control of that flow. Presently used models usually base on the Galerkin method, where the flow is approximated by the number of modes and coefficients. The velocities are computed from a system of ordinary differential equations, called Galerkin System, instead of Navier‐Stokes equation. In this paper, reduced order models of the flow around NACA‐0012 airfoil are presented. The chosen mode sets include POD modes from Karhunen‐Loeve decomposition (which require previous direct numerical simulation), as well as different eigenmodes from global stability analysis of the flow.First Published Online: 14 Oct 2010